Health literacy and warfarin therapy at two anticoagulation clinics in Brazil. Issue 14 (3rd March 2017) - Martins, Maria Auxiliadora Parreiras; Costa, Josiane Moreira; Mambrini, Juliana Vaz de Melo; Ribeiro, Antonio Luiz Pinho; Benjamin, Emelia J; Brant, Luisa Campos Caldeira; Paasche-Orlow, Michael K; Magnani, Jared W
Abstract : Objective: Health literacy has been related to health-related conditions and health outcomes. Studies examining the association of health literacy and anticoagulation have had variable results. We sought to investigate the relations of health literacy and percentage of time in therapeutic range (TTR) in a vulnerable Brazilian cohort at two hospital-based anticoagulation clinics. Methods: We measured health literacy with the Short Assessment of Health Literacy for Portuguese-speaking Adults (SAHLPA-18) in 2015–2016. We identified the demographic and clinical characteristics associated with health literacy and related health literacy to TTR. Results: We enrolled 422 adults prescribed chronic warfarin therapy in our observational study (median age 62.1 years; 58.8% women; monthly income $200.00). The prevalence of inadequate health literacy (score 0–14 points) was 72.3% with a median score of 12 (quartiles, Q1=10; Q3=15) on the SAHLPA-18. The median TTR was 66.1%. In the multivariable logistic analysis, cognitive impairment and assistance with taking warfarin were associated with inadequate health literacy. Prosthetic heart valves and more school years were associated with adequate health literacy. Our analyses showed no significant relation between health literacy and TTR, analysing health literacy as a categorical (adjusted OR 1.05; 95% CI 0.65 to 1.70) or continuous variable (Spearman's coefficient 0.02; p=0.70). Conclusions: Inadequate health literacy was highly prevalent in this impoverished Brazilian cohort receiving anticoagulation with warfarin. However, we did not identify an association between health literacy and TTR. Future investigations may consider the systemic factors that contribute towards successful anticoagulation outcomes for vulnerable patient cohorts with inadequate health literacy.